Perbaungan Irrigation Network Information System Regency Serdang Bedagai - Geri Aldian Sagala; Achwil Putra Munir; Saipul Bahri Daulay (Jurnal Rekayasa Pangan dan Pertanian, 2013)
Information system in Perbaungan irrigated area still done manually, so the storage, processing and delivery of information to be ineffective and inefficient. In the information management most the result were done by human role and took a relatively longer time. Moreover, the information seekers-and decision-makers also have difficulty in obtaining the data they need. Therefore, it is necessary to further develop of the information system. Web-based information system is considered to be a solution in order to access information faster, systematicaly and easy to use. For that a web-based information systems in the management of irrigation in Perbaungan irrigation areas Serdang Bedagai Regency was designed. Irrigated network information system was designed using PHP programming language, MySQL database and the method of system development life cycle (SDLC). Key words: information system, irrigation system, Perbaungan irrigated area, web